OUTCOME AND COMPLICATIONS OF SNODGRASS REPAIR CONCERNING UC FISTULA AND COMPLETE BREAKDOWN - JALANEE , R; CHOUDHARY , MA; ARIF , K; KHAN , I; NAJEEBULLAH , D; KAKAR , SU (Biological and Clinical Sciences Research Journal, 2024)
Male urethral hypospadias is a common congenital disease requiring surgical correction. Because of its versatility, superior aesthetic outcomes, and low rate of complications, the Snodgrass (TIP) repair procedure is commonly utilized. However, complications, including urethrocutaneous (UC) fistula and total breakdown are still major worries. Objective: To evaluate the outcomes and complications of the Snodgrass repair for hypospadias, focusing on urethrocutaneous fistula formation, wound infections, and total breakdown. Methods: A total of 56 kids who received Snodgrass repair for hypospadias at a Quetta tertiary care facility between 2020 and 2023 were included. The study focused on UC fistulas, wound infections, and total breakdowns, examining surgical techniques, complications, and post-operative results. Results: In 26.7% of cases, UC fistula was the most frequent complication, followed by bleeding (10.7%) and wound infections (5.3%). Though uncommon, total breakdown was noted in 3.5% of cases. 75% of parents expressed satisfaction with the cosmetic results, and 10.7% were very satisfied. Additionally, the study found that complications varied with age, with the largest risk of UC fistula occurring in younger children (6–18 months). Conclusion: When used to correct distal hypospadias, the Snodgrass procedure has good functional and aesthetic results. Nonetheless, to reduce problems and increase long-term success, the study highlights the necessity of better surgical methods, preoperative planning, and postoperative care.